2022
DOI: 10.1007/s11538-022-01064-w
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Age-Specific Vaccination Strategies and Post-vaccination Reopening Policies for COVID-19 Control Using SEIR Modeling Approach

Abstract: As the availability of COVID-19 vaccines, it is badly needed to develop vaccination guidelines to prioritize the vaccination delivery in order to effectively stop COVID-19 epidemic and minimize the loss. We evaluated the effect of age-specific vaccination strategies on the number of infections and deaths using an SEIR model, considering the age structure and social contact patterns for different age groups for each of different countries. In general, the vaccination priority should be given to those younger pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…A few studies tailor their model to more than one country to showcase how variability in e.g. age distributions, age-stratified contact patterns, or implemented NPIs can affect optimal vaccine prioritization, see e.g., Gozzi et al (2021); Liu et al (2022b); Wang et al (2022); Liu et al (2022a). Other studies employ more abstract models, frequently ABMs, which are not tailored to any specific setting, see e.g., Romero-Brufau et al (2021); Grauer et al (2020); Kadelka and McCombs (2021).…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…A few studies tailor their model to more than one country to showcase how variability in e.g. age distributions, age-stratified contact patterns, or implemented NPIs can affect optimal vaccine prioritization, see e.g., Gozzi et al (2021); Liu et al (2022b); Wang et al (2022); Liu et al (2022a). Other studies employ more abstract models, frequently ABMs, which are not tailored to any specific setting, see e.g., Romero-Brufau et al (2021); Grauer et al (2020); Kadelka and McCombs (2021).…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…Several SEIR models reported that address modeling, simulations, and forecast of COVID-19 epidemics, 72 the effects of public health measures, 73 dynamic updates of the model using daily data for epidemic forecasting, 74,75 and simulations to assess the effects of public health measures 70,76 or their combinations, 29 vaccination, 74,77 and multiwave epidemic modeling. 78,79 The main enhancements used for epidemic modeling involve the use of machine learning for epidemic forecasting, 74,75,80 and the use of proxy measurements for the assessment of epidemic parameters such as tracing mobility from social networks, 81,82 assessing vaccination rates, 83 or using simulations to assess different epidemic scenarios while changing relevant parameters.…”
Section: Comparison With the Prior Workmentioning
confidence: 99%
“…Compared to the Susceptible, Exposed, Infectious (SIR) model and the classic Susceptible, Exposed, Infectious, Recovered (SEIR) model, the generalized SEIR model ( 13 ) is more appropriate to reflect the transmission dynamics of COVID-19 ( 14 ), which accounts for some important characteristics of the disease, such as the latency period, death, quarantine for confirmed cases, and the protection rate of susceptible populations. Some efforts have been devoted to predict the effectiveness of various preventive strategies against COVID-19 transmission in the general population by the generalized SEIR model ( 15 20 ). By adjusting the protection rate of the SEIR model, the impact of vaccination ( 15 20 ) and non-pharmaceutical interventions (NPIs) ( 15 , 16 , 18 , 20 ) have been simulated.…”
Section: Introductionmentioning
confidence: 99%
“…Some efforts have been devoted to predict the effectiveness of various preventive strategies against COVID-19 transmission in the general population by the generalized SEIR model ( 15 20 ). By adjusting the protection rate of the SEIR model, the impact of vaccination ( 15 20 ) and non-pharmaceutical interventions (NPIs) ( 15 , 16 , 18 , 20 ) have been simulated. The results of some studies suggest that the effectiveness of vaccination depends on the efficacy of the vaccines used and the coverage of vaccination ( 15 , 17 19 ); if the population cannot be fully covered by effective vaccination, combining vaccination and NPIs is an ideal measure to reduce the number of confirmed cases and deaths of COVID-19 ( 15 , 16 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation